Understanding how to create healthier places: A qualitative study exploring the complex system of urban development decision-making. (May 2023) - Le Gouais, Anna; Bates, Geoff; Callway, Rosalie; Kwon, Heeseo Rain; Montel, Lisa; Peake-Jones, Sian; White, Jo; Hasan, Md Nazmul; Koksal, Caglar; Barnfield, Andrew; Bondy, Krista; Ayres, Sarah
Abstract: Tackling complex system challenges like creating healthy environments requires understanding priorities and structures affecting multiple actors. This qualitative study, involving 132 multi-sectoral stakeholders spanning the urban development decision-making system, explores how to influence healthier place-making. Using thematic analysis we develop themes around competing stakeholder priorities; structural 'rules' and influential relationships; and justifying a focus on health, requiring greater clarity and consensus around definitions of 'healthy' urban development. Building on the socio-ecological model we highlight how a multi-faceted approach is required for change at multiple levels in the complex system to target individual actor motivations, organisational priorities and structural 'rules'. Highlights: Urban development stakeholders have competing priorities that may not prioritise health and wellbeing. Policies and legislation may not incentive healthy decision-making. A complex system approach identifies multiple leverage points for healthy place-making: target inidividuals, organisations and structures. More clarity and consensus around definitions of 'healthy' urban development needed.